The Effect of Tax Planning and Profitability on Company Value with Good Corporate Governance as a Moderating Variable - Suyanto; Emilia, Risty; Pratama, Yhoga Heru; Putri, Fuadhillah Kirana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This research aims to investigate the impact of Tax Planning and Profitability on a company's value, with Good Corporate Governance (GCG) serving as a moderating factor. The purpose of this investigation is to gain insight into how tax regulations and profitability impact corporate value, along with the contribution of effective governance in managing this relationship. By employing quantitative techniques, the study analyzes secondary information from 61 manufacturing firms registered on the Indonesia Stock Exchange (IDX) from 2019 to 2023, utilizing various methods, including linear regression and moderated regression analysis (MRA). The findings reveal that Tax Planning positively and significantly affects a company's value. However, there is a lack of evidence suggesting that profitability has a considerable effect on corporate worth. Furthermore, GCG has a significant negative moderating effect on the relationship between tax planning and company value, indicating that the positive effects of tax planning might be diminished. On the other hand, GCG shows a substantial positive impact on the relationship between a firm's value and profitability. This research concludes that while Tax Planning is vital for enhancing company value, the application of GCG may influence this relationship.